On Doubt - Flusser, Vilem, 1920-1991 (Book collections on Project MUSE., 2014)
In On Doubt, Vilem Flusser refines Martin Heidegger's famous declaration that "language is the dwelling of Being." For Flusser, "the word is the dwelling of being," because in fact, in the beginning, there was the word. On Doubt is a treatise on the human intellect, its relation to language, and the reality-forming discourses that subsequently emerge. For Flusser, the faith that the modern age places in Cartesian doubt plays a role similar to the one that faith in God played in previous eras-a faith that needs to be challenged. Descartes doubts the world through his proposition cogito ergo sum.